Integrated Management of Processes and Information - Shaw, Kenneth A (Business Expert Press, 2013)
Ebook from IG Library ; Many process management books focus on manufacturing applications. A few discuss services applications and occasionally some comment on the information processes outside of the normal information technology (IT) function. When a business seeks to improve the processes it uses in order to provide efficiency and cost savings to a product or service, that business needs to consider its manufacturing, service, and information handling processes together because they are not independent. This book has two goals: First, to help business practitioners integrate their management of manufacturing or service processes with information processes; and second, to provide business schools with a textbook that can be used for a basic process management course to precede or accompany the typical operations management course Because information handling approaches vary considerably with organizational size, both large and small business approaches are discussed. This discussion is focused on basic concepts rather than specific technical aspects like what type of information hardware to be used. One chapter will discuss the considerations necessary when adding information process management to enterprise resource planning (ERP), statistical process control (SPC), and supply chain logistics approaches from both large and small business perspectives.